Defective assembly and intracellular transport of mutant paramyxovirus hemagglutinin-neuraminidase proteins containing altered cytoplasmic domains. - Parks, G D (1990)
The hemagglutinin-neuraminidase (HN) integral membrane protein of paramyxoviruses is expressed at the cell surface as a tetramer consisting of a pair of disulfide-linked dimers. HN has a large C-terminal ectodomain, a 19-residue uncleaved signal-anchor domain, and a 17-residue N-terminal cytoplasmic tail. Various mutant HN genes were constructed to examine the role of residues flanking the signal-anchor domain, including the cytoplasmic tail, on assembly and intracellular transport of the HN glycoprotein. Expression of the altered genes showed that by 90 min after synthesis the majority of the mutant HN proteins were in a conformationally mature form as assayed by their reactivity with conformation-specific monoclonal antibodies. However, the mutant proteins showed varied endoplasmic reticulum-to-Golgi apparatus transport rates, ranging from that of wild-type HN (t1/2 approximately 90 min) to slowly transported molecules (t1/2 approximately 5 h) and to molecules in which transport was not detected. Pulse-chase experiments indicated that the altered HN molecules had a specific and transient interaction with the resident endoplasmic reticulum protein GRP78-BiP, and thus the altered HN molecules were not retained in the endoplasmic reticulum by a prolonged interaction with GRP78-BiP. Sucrose density gradient sedimentation analysis of the mutant HN molecules indicated that they all had an oligomeric form that differed from that of wild-type HN; most of the molecules were found as disulfide-linked dimers rather than as tetramers. These data suggest that the HN cytoplasmic tail may function in the assembly of the final transport-competent oligomeric form of HN and that mutant HN molecules with seemingly properly folded ectodomains are retained in the endoplasmic reticulum by an as yet unidentified mechanism. The possible role of the HN cytoplasmic tail as a signal for intracellular transport is discussed.